Prediction of air pollution of Ahwaz City by improving energy efficiency - Javadzadeh, Mahmoud (2014)
Since the development of industries, vehicles and the people in the cities and their suburban areas, carbon monoxide, sulfur dioxide, nitrogen dioxide and some other pollutants have been increasing. This study has been conducted to predict the air pollution, utilizing model of atmospheric pollutant dispersion for a large city of Ahwaz, with regard to land use, the amount of pollutants released from point, area and line sources, subsequently integrated mesoscale model was used to predict the dispersion and concentration of the air pollutants. The main purpose of the study was to determine the dispersion factors and the meteorological condition which cause the air to be polluted over the study area. To achieve the main goal of the study, establishment of the emission inventory, meteorological simulation and (CO), (NO, NO2) and SO2 dispersions sources in the Ahwaz city regions by using the WRF CAMx and evaluation of the model performance were done. The mean difference between prediction and observed data was obtained by Root Mean Square Error (RMSE) and the Peak results are as follow: SO2, 75 ppb, NO2, 100 ppb, NO, 85 ppb and CO, 40 ppb. A comparison of the observed peaks from the air pollution measurement stations at ground level, and the results of WRF / CAMx model show the error of the peaks is less than 30%, which this percentage indicates that input data to the model and to the real data are close to each other. Normalized error was ±20% and normalized bias was between -15% to +15%, this amount for the air pollution models are acceptable. Also, the BIAS ERROR calculates the relationship coefficient between the simulated prediction and actual data. The results showed that the Zergan Power Plant has more effect over the North East part of the Ahwaz city than the Ramin Power Plant, due to distances and the wind direction characteristics and that the pollutants concentration is equally related to emitted pollutants from their own sources. The Ahwaz city line sources have the most effect on the central city, concerning the four pollutants. It can be concluded that the concentration of SO2 and NO2are higher than the NAAQS (National Ambient Air Quality Standards) value for SO2 (75 ppb) and NO2 (100 ppb) and other pollutants level are within the limit.